Gender-gaps and glass ceilings: A survey of gender-specific publication trends in Psychiatry between 1994 and 2014 - Süßenbacher, S.; Amering, M.; Gmeiner, A.; Schrank, B. (European psychiatry, 2017)
Within academic psychiatry, women are underrepresented in the higher academic ranks. However, basic determinants of women's lack of academic advancement such as publication activity are poorly understood. The present study examines women's publication activity in high-impact psychiatry journals over two decades and reports developments in the numbers of male and female authorship over time and across cultural areas. We conducted a retrospective bibliometric review of all articles published in 2004 and 2014 in three high-ranking general psychiatry journals. Statistical comparisons were made between the two years and with results from a baseline assessment in 1994. The overall percentage of female authors increased from 24.6% in 1994 to 33.2% in 2004 to 38.9% in 2014. Though increases in female authorship were statistically significant for both decades, there was less difference between 2004 and 2014, indicating a possible ceiling effect. Rates of female first authors increased between 1994 and 2014, though to a lesser degree between 2004 and 2014. Numbers of female corresponding authors plateaued between 2004 and 2014. Within Europe, Scandinavia displayed the most balanced gender-wise first author ratios. Western European and Central European countries increased their rates of female first authors substantially between 2004 and 2014. Despite gains in some areas, our study reveals considerable deficits in the diversity of the current academic psychiatric landscape. Ongoing efforts and interventions to enhance the participation of underrepresented groups on institutional, political and editorial levels are necessary to diversify psychiatric research.